Le Collezioni Digitali del FAI ad HaltaDefinizione: un patrimonio nel patrimonio - MediaGEO, Redazione (Archeomatica, 2024)
The acquisition technologies developed by Haltadefinizione allow you to obtain very high resolution digital images of the paintings. Thanks to specially designed algorithms, in fact, it is possible to combine a large quantity of individual photographic shots of small portions of the portraits to obtain what is called a gigapixel image.